Pendampingan Penyusunan Laporan Keuangan BUMDES - Yoksan Susanto; Niluh Putu Evvy Rossanty; Maskuri Sutomo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This activity is motivated by the author's observations regarding the management of BUMDES which is still underutilized, because there are some people who do not participate in advancing, managing and developing village-owned enterprises which can later hamper the economy of a village. The purpose of this activity is to find out the role of BUMDES in improving the economy, to find out the supporting and inhibiting factors of BUMDES in improving the economy. This activity was carried out under the MBKM program by going directly to the field for five months. The population in this study are members of BUMDES Kaliburu. With interview techniques, documentation and observation. The results of the mentoring activity for the preparation of financial reports with the theme